Neural substrates involved in the control of posture. (17th January 2017) - Takakusaki, Kaoru; Takahashi, Mirai; Obara, Kazuhiro; Chiba, Ryosuke
Abstract: This review argues neuronal mechanisms of postural control. Multi-sensory information such as somatosensory, visual, and vestibular sensation act on various areas of the brain so that adaptable postural control can be achieved. Automatic process of postural control, which is termed as postural reflexes including head–eye coordination accompanied by appropriate alignment of body segments, is mediated by the descending pathways from the brainstem. Cooperation of the vestibulospinal, reticulospinal, and tectospinal tracts contributes to this process. On the other hand, walking in unfamiliar circumstance requires cognitive process of postural control, which depends on knowledge of self-body, such as body schema, sense of postural verticality, and body motion in space. Such a bodily cognitive information is produced at the temporoparietal cortex. They are fundamental to sustention of vertical posture and construction of motor programs. The programs then run to execute anticipatory postural adjustment which is appropriate for achievement of goal-directed movements. The basal ganglia and cerebellum may affect both the automatic and cognitive processes of postural control through reciprocal connections with the brainstem and cerebral cortex, respectively. Consequently, impairments in cognitive function in addition to damages in the motor cortex, basal ganglia, and cerebellum may disturb appropriate postural control, resulting in falling.